Motivation as a labor efficiency factor - S.A. Maslova; K.E. Kononiuk (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2018)
The article deals with the issues of labor motivation. Motivation, as a process of influence on a worker-person, occupies an important place in the system of enterprise management, personnel management and labor management. The essence of motivation is defined as a set of inductive causes, factors influenced by an employee in a particular situation. The authors substantiate the role of needs, interests, values and motives in creating conditions for effective work, which necessarily includes the quality of work. Moreover, in today's conditions, effective quality work is decent work. The main approaches to the definition of the concept of «motivation» are presented and the essence of material and non-material motivation at the enterprise is disclosed. The paper explains the need for a systematic approach to the formation of types of motivation, needs, motives, incentives, modern worker who strives not only for material wealth but also wants to be engaged in interesting, meaningful work, to enjoy it. Describing the main theories of motivation, the authors substantiate the possibility of their use in practical activities to create conditions for effective work at the enterprise. Motivation is considered as the factor of labor efficiency.